Force Degradation Study of Tenofovir Disoproxil Fumarate by UV-Spectrophotometric Method - D, Debaje Priyanka; H, Chavan Harishchandra (Asian Journal of Pharmaceutical Research and Development, 2020)
Tenofovir disoproxil Fumarate (TDF), acyclic phosphonate nucleotide analogue, used as antiretroviral agents in the treatment of HIV-1 infection. A stability indicating UV -spectrophotometric method is simple, an accurate and economic, precise and reproducible method has been used for the estimation of Tenofovir disoproxil Fumarate in bulk and tablets dosage form in present work. The wavelength selected for the absorption correction method was 260 nm. The linearity range of 2-10μg/ml proved that it obeyed Beer’s Law and the correlation coefficient (r2) was found to be 0.999 at 260 nm. The drug was subjected to acid, alkali, peroxide, UV and Heat degradation. The force degradation studies of Tenofovir disoproxil Fumarate was done on Stress degradation by hydrolysis under alkaline condition by using 0.1N NAOH was found to be 10.6%. Stress degradation by hydrolysis under acidic condition by using 0.1N HCl and product degradation was found to be 10.95%. Oxidative degradation was done by using hydrogen peroxide and product degradation was found to be 12.22%. Neutral hydrolytic degradation was found to be 12.26%. Forced degradation studies of drug reveal good stability under the chosen experimental conditions.